Covid Data Analytics Repository: An interdisciplinary look into the COVID-19 pandemic in Brazil - A. S. Franco, Ramon; Loures Alzamora, Pedro; Guiginski, Janaína; L. T. P. Cunha, Evandro; Bernardes, Tereza; Galindo, Juan F.; Passos, Luana; Schneider, Raquel; Chagas, Bruno; Ferreguetti, Kícila; Cardoso, Luísa; Moreira, Pedro; et al. (Journal of Information and Data Management, 2022)
This article describes the construction and deployment of the Covid Data Analytics Repository, a source for interdisciplinary studies about the impact of the COVID-19 pandemic in Brazil. We collected different types of data from official (IBGE, DATASUS) and non-official (Brasil.IO) sources, online social networks (Instagram, Twitter), and from a search engine analysis tool (Google Trends). We used these data to perform investigations aimed to understand the impacts of COVID-19 in the country, from economics to social behavior. At the moment of publication of this article, our repository contains 1,508 documents, classified into two main types: (i) databases and tables downloaded from the aforementioned sources; and (ii) papers, reports, maps and graphs resulting from the analyses that we performed. As a means to allow reproducibility and foster follow-up studies, we released our repository for public use.